La naissance des cités-royaumes Cypriotes - Petit, Thierry (Archaeopress Publishing Ltd., 2019)
This book analyses the causes, characteristics and chronology behind the emergence of Iron Age Cypriot city-kingdoms. It suggests the received autochthonous theory is not supported by archaeological or textual evidence, and posits a more nuanced variant of the Phoenician theory, placing Cyprus as a relay point between the Levant and Aegean worlds.